The Reality of Competitive Advantage in Secondary Government Schools in Al-Mafraq Governorate: A Field Study on the Principals of Public Schools in Mafraq Governorate – Jordan - Al-khawaldeh, Fayez Suleiman (Journal of Educational and Psychological Sciences, 2020)
The study aimed at finding out the reality of competitive advantage in secondary government schools in Al-Mafraq Governorate, the survey method was used, and the questionnaire was the study tool, the study sample consisting of (153) principals, the study results showed that the reality of competitive advantage in secondary government schools in Al-Mafraq Governorate from the point of view of the study sample individuals got a total average score (2.73 out of 5) i.e. a degree at the level of fields; the field of leadership got the highest average; (2.90 out of 5) followed by The field of human resources management with an average of (2.73) and thirdly, the field of quality; with an average of (2.65) and finally the field of technology with an average of (2.62), all of which are verbal (average). Also, there were no statistically significant differences in the estimates of the study sample individuals for the reality of the competitive advantage in government schools due to the gender variable; on the overall level of the tool and on all fields and based on the results of the study, the researcher presented a set of recommendations and proposals, The need to keep abreast of what is new to develop school performance in the light of competitive advantage.